고등학교 교육과정의 전문교과 외국어 계열 과목 재구조화 방안 연구: 해외 외국어 심화 과목 분석 및 외국어고 교사 F.G.I.를 중심으로 - 김석영; Kim Sok-yong; 이주연; Lee Joo-youn (언어와 정보 사회, 2021)
This study is the result of exploring ways to restructure specialized foreign language subjects and courses in the high school curriculum based on the analysis of overseas curriculums and F.G.I. for teachers. Education in Korea is currently preparing to implement curriculum reform and changes in education policies related to specialized subjects following the introduction of the high school elective credit system. Accordingly, this paper analyzes the system and characteristics of advanced foreign language subjects in Ontario, Canada, New South Wales, Australia, and Singapore, and analyzes the contents of the F.G.I. for teachers in the foreign language high schools. Based on the analysis, this paper suggests diversification of subject options and reinforcement of content-based subjects as a way to restructure specialized foreign language subjects and courses.